Kepemimpinan Kiai Dalam Mengembangkan Wirausaha Di Pesantren - Muhammad Amin Nur; Nurul Yaqien (J-MPI (Jurnal Manajemen Pendidikan Islam), 2023)
Entrepreneurship development in Pesantren (Islamic boarding schools) is an important thing to do so that they become independent. This study aims to reveal and elaborate on three things, namely: the concept of kiai leadership in developing entrepreneurship in pesantren; strategies for developing entrepreneurship in pesantren; and the benefits obtained by pesantren and the surrounding community with the development of entrepreneurship in pesantren. The data were obtained from two pesantrens that have been successful in developing entrepreneurship, namely pesantren Sidogiri and pesantren An Nur 2. Data collection is done through interviews, observation, and documentation. All data were analyzed using domain and componential analysis techniques. The results of the data analysis show that the kiai's concept for developing entrepreneurship in pesantren is collective-collegial, democratic-participatory, and consultative-authoritative. While the strategy carried out by the Kiai is to build and maintain trust, empowerment, synergy, innovation, flexible policies, and solid cooperation. The benefits of the results of entrepreneurship development in pesantren are felt and enjoyed by various parties, namely: first, the availability of basic necessities for students, alumni, teachers, pesantren and surrounding communities. Second, the opening of new job opportunities for the community, especially residents around the pesantren. Third, pesantren have economic independence, so that they are authoritative and independent in regulating and managing pesantren. The research has implications for the development of entrepreneurship based on religious values.